Association of the Estimated Glomerular Filtration Rate With vs Without a Coefficient for Race With Time to Eligibility for Kidney Transplant - Zelnick, Leila R. (JAMA Netw Open, 2021)
IMPORTANCE: Kidney transplant is associated with improved survival and quality of life among patients with kidney failure; however, significant racial disparities have been noted in transplant access. Common equations that estimate glomerular filtration rate (eGFR) include adjustment for Black race; however, how inclusion of the race coefficient in common eGFR equations corresponds with measured GFR and whether it is associated with delayed eligibility for kidney transplant listing are unknown. OBJECTIVE: To compare eGFR with measured GFR and evaluate the association between eGFR calculated with vs without a coefficient for race and time to eligibility for kidney transplant. DESIGN, SETTING, AND PARTICIPANTS: This prospective cohort study used data from the Chronic Renal Insufficiency Cohort, a multicenter cohort study of participants with chronic kidney disease (CKD). Self-identified Black participants from that study were enrolled between April 2003 and September 2008, with follow-up through December 2018. Statistical analyses were completed on November 11, 2020. EXPOSURE: Estimated GFR, measured annually and estimated using the creatinine-based Chronic Kidney Disease-Epidemiology (CKD-EPI) equation with and without a race coefficient. MAIN OUTCOMES AND MEASURES: Iothalamate GFR (iGFR) measured in a subset of participants (n = 311) and time to achievement of an eGFR less than 20 mL/min/1.73 m(2), an established threshold for kidney transplant referral and listing. RESULTS: Among 1658 self-identified Black participants, mean (SD) age was 58 (11) years, 848 (51%) were female, and mean (SD) eGFR was 44 (15) mL/min/1.73 m(2). The CKD-EPI eGFR with the race coefficient overestimated iGFR by a mean of 3.1 mL/min/1.73 m(2) (95% CI, 2.2-3.9 mL/min/1.73 m(2); P < .001). The mean difference between CKD-EPI eGFR without the race coefficient and iGFR was of smaller magnitude (−1.7 mL/min/1.73 m(2); 95% CI, −2.5 to −0.9 mL/min/1.73 m(2)). For participants with an iGFR of 20 to 25 mL/min/1.73 m(2), the mean difference in eGFR with vs without the race coefficient and iGFR was 5.1 mL/min/1.73 m(2) (95% CI, 3.3-6.9 mL/min/1.73 m(2)) vs 1.3 mL/min/1.73 m(2) (95% CI, −0.3 to 2.9 mL/min/1.73 m(2)). Over a median follow-up time of 4 years (interquartile range, 1-10 years), use of eGFR calculated without vs with the race coefficient was associated with a 35% (95% CI, 29%-41%) higher risk of achieving an eGFR less than 20 mL/min/1.73 m(2) and a shorter median time to this end point of 1.9 years. CONCLUSIONS AND RELEVANCE: In this cohort study, inclusion of the race coefficient in the estimation of GFR was associated with greater bias in GFR estimation and with delayed achievement of a clinical threshold for kidney transplant referral and eligibility. These findings suggest that nephrologists and transplant programs should be cautious when using current estimating equations to determine kidney transplant eligibility.